Efectos económicos del dengue en Colombia: un análisis a nivel de municipios durante el periodo 2007-2017 (2021)
This document aims to identify the economic impact that dengue fever had on the finances of Colombia's municipalities during the epidemic peaks that occurred in the period 2007-2017. The methodology consisted of an impact evaluation of the type differences in differences with continuous treatment. Thus, the interaction between two variables, the capacity of the mosquito to survive below 1,800 meters above sea level (M.S.N.M) and the epidemic peaks of the disease, was used to create a treatment group: municipalities below 1,800 M.S.N.M where dengue can be considered endemic; and a control group: municipalities above this height, where the appearance of the disease is exceptional. The results show that the current income per capita of the affected municipalities decreased by 32,662 colombian pesos in the study period, 7% lower than the average...